Pembuatan Minyak Aromaterapi dari Bunga Soka untuk Peluang Berwirausaha - Melina Wati; Agus Susanti; Nurulisma Saputri (Garina, 2025)
Apart from being a living fence, the benefits of the soka plant are that the flowers can be used as a relatively cheap aromatherapy ingredient because the soka plant is easy to find, especially on the side of the road, and has a fragrance almost like ylang-ylang flowers. Data collection uses Observation, Literature, Experimentation, Documentation, Interviews, Questionnaires, and data analysis uses descriptive qualitative methods. The results of the sensory test assessment of aspects of color, texture, aroma and ease of use, as many as 3 expert validators preferred experimental product 3 with a total rating of 17 (very suitable). The results of the public test showed that people's acceptance was at the highest level of liking in experiment 3 with a total average with color aspects of 4.123 which means like it, texture 3.775 which means quite like it, aroma 4.4 which means like it, ease of use 4.65 which means like it , and a pack of 4,825 which means likes, so that it can become an entrepreneurial opportunity. The conclusion from research on the use of soka flowers is that the resulting aromatherapy oil can be used as a mixture in aromatherapy candles, used in reed diffusers, humidifiers and aromatherapy furnaces. And from the results of research on the use of soka flowers to make aromatherapy oil, it is hoped that it can later be used as other forms of aromatherapy such as candles and soap, and can be developed for further research.